2022
DOI: 10.3390/app12031537
|View full text |Cite
|
Sign up to set email alerts
|

Light Reflectance Characterization of Waste Glass Coating for Tiles

Abstract: Glass wastes that come from recycling plants do not often find a proper use, thus, they are discarded. In order to find future uses for these wastes, this paper explores the characterization of waste glasses (WGs) as a raw material through the assessment of their light reflectance if they were used for external coatings in building materials. To this aim, in this research, several clay-tile specimens were fabricated and coated with three different compositions of waste glass. For these specimens, three variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The spectrometer works in the radiation range of 350-1100 nm, taking measurements for the VIS and NIR radiation according to ASTM E903 standard for laboratory measurements [36]. All the experimental set up is presented in the previous study [33]. The colorimetric coordinates of the samples representing WG1, WG2 and the reference were determined in compliance with the CIE-1976 l*a*b* colorimetric method defined by the international commission on Illumination (CEI EN 60335-2-27).…”
Section: Tiles Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrometer works in the radiation range of 350-1100 nm, taking measurements for the VIS and NIR radiation according to ASTM E903 standard for laboratory measurements [36]. All the experimental set up is presented in the previous study [33]. The colorimetric coordinates of the samples representing WG1, WG2 and the reference were determined in compliance with the CIE-1976 l*a*b* colorimetric method defined by the international commission on Illumination (CEI EN 60335-2-27).…”
Section: Tiles Characterizationsmentioning
confidence: 99%
“…This research builds on the previous findings of a prior work, where a preliminary characterization of sample clay specimens covered with WG (small square samples covered with WG) was performed in terms of the influence of the following parameters: the type of WG, the temperature and holding time of firing treatment, and thickness of WG coating. This present work represents the main stage of the research using real shape of roof tiles, where the starting point is based on the best experimental results obtained from the characterization of different samples clay tiles reported in [33], i.e. by using the optimal combinations of parameters, and using only those two types of WG that showed good results and a firing temperature of 1000 • C.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, waste glass cullet was successfully mixed with conventional materials to fabricate sustainable asphalt roof shingles, which have a solar reflectance greater than 25%, and better solar reflectance properties [45]. Recent research has shown that the use of waste glass tile coatings should be considered for a global solar reflectance analysis [123]. Future studies are needed to evaluate the influence of using waste glass on the solar radiation reflectance in ceramic materials, especially in the NIR solar spectrum, where 52% of the solar energy is concentrated.…”
Section: Country Of Affiliationmentioning
confidence: 99%
“…Another example is the integration of glass in the fabrication of ceramic materials as fine particles with optimal dosage and particle size, in order to enhance their physical, mechanical, and thermal properties and improve the solar reflectance performance [9]. The design of ceramic tiles with recycled glass could contribute to the production of friendly construction materials to be applied in the design of cool surfaces [10], i.e., surfaces with reflective materials and coatings that reflect the solar energy radiation that hits building envelopes and urban areas [11], including roofs, facades, and pavements. Such materials are able to reduce the thermal infrared radiation outflow in the atmosphere, as well as the temperature and the solar heat gain, in order to palliate the UHI effect [12].…”
Section: Construction Phase Of Building: Using New Materials For Buil...mentioning
confidence: 99%